2023
DOI: 10.21873/invivo.13206
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-to-lymphocyte Ratio Predicts the Outcomes of Hypopharyngeal Squamous Cell Carcinoma Treated With Definitive Radiotherapy

Abstract: Background/Aim: Previous studies have identified several inflammatory biomarkers that are useful as prognostic biomarkers for various cancer types. However, the fibrinogen-to-lymphocyte ratio (FLR) has not been addressed in head and neck squamous cell carcinoma. Here, we aimed to examine the value of pretreatment FLR as a prognostic marker in patients who received definitive radiotherapy for hypopharyngeal squamous cell carcinoma (HpSCC). Patients and Methods: This retrospective study included 95 patients trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Accumulating studies have suggested that systemic inflammation promotes tumor progression and metastasis via the inhibition of apoptosis, promotion of angiogenesis, and damaging of DNA (87). Pretreatment hematological markers of inflammatory response, which can be measured by routine blood examinations, such as neutrophils, monocytes, lymphocytes, platelets, fibrinogen, and albumin, and several of these markers combined, have emerged as useful prognostic factors for patients with head and neck carcinomas (21,25,(27)(28)(29)(30)(31)(88)(89).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have suggested that systemic inflammation promotes tumor progression and metastasis via the inhibition of apoptosis, promotion of angiogenesis, and damaging of DNA (87). Pretreatment hematological markers of inflammatory response, which can be measured by routine blood examinations, such as neutrophils, monocytes, lymphocytes, platelets, fibrinogen, and albumin, and several of these markers combined, have emerged as useful prognostic factors for patients with head and neck carcinomas (21,25,(27)(28)(29)(30)(31)(88)(89).…”
Section: Discussionmentioning
confidence: 99%